The toxicity and distribution of iron oxide–zinc oxide core‐shell nanoparticles in C57BL/6 mice after repeated subcutaneous administration. Issue 6 (8th January 2015) - Yun, Jun‐Won; Yoon, Jung‐Hee; Kang, Byeong‐Cheol; Cho, Nam‐Hyuk; Seok, Seung Hyeok; Min, Seung‐Kee; Min, Ji Hyun; Che, Jeong‐Hwan; Kim, Young Keun
Abstract: Therapeutic cancer vaccines promote immune responses by delivering tumour‐specific antigens. Recently, we developed iron oxide (Fe3 O4 )–zinc oxide (ZnO) core‐shell nanoparticles (CSNPs) as carriers for antigen delivery into dendritic cells (DCs), and the CSNPs were injected subcutaneously into C57BL/6 mice to examine the systemic toxicity, tissue distribution and excretion of the CSNPs. The doses injected were 0, 4, 20 and 200 mg kg –1 weekly for 4 weeks. No significant changes were observed after the CSNPs administration with respect to mortality, clinical observations, body weight, food intake, water consumption, urinalysis, haematology, serum biochemistry, and organ weights. A dose‐dependent increase in granulomatous inflammation was observed at the injection site of the CSNP‐treated animals, but no other histopathological lesions in other organs could be attributed to the CSNPs. The Zn concentration, which is an indicator for CSNPs, was not significantly higher in the sampled tissues, urine, or faeces after the CSNP injection. In contrast, the Zn concentration at the subcutaneous skin of the site injected with the CSNPs increased in a dose‐dependent manner, along with a macroscopic deposition of the CSNPs. The CSNP residue at the injection site resulted in a foreign body response with the appearance of macrophage infiltration, but otherwise did not show any systemic distribution or toxicity at up to 200 mg kg –1 during this study. In conclusion, CSNPs could be used as good antigen carriers for DC‐based immunotherapy, although further study is needed to completely clear the residue of the CSNPs at the injection site. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Therapeutic cancer vaccines promote immune responses by delivering tumour‐specific antigens. Recently, we developed iron oxide (Fe3 O4 )–zinc oxide (ZnO) core‐shell nanoparticles (CSNPs) as carriers for antigen delivery into dendritic cells (DCs), and the CSNPs were injected subcutaneously into C57BL/6 mice to examine the systemic toxicity, tissue distribution and excretion of the CSNPs. The doses injected were 0, 4, 20 and 200 mg kg –1 weekly for 4 weeks. No significant changes were observed after the CSNPs administration with respect to mortality, clinical observations, body weight, food intake, water consumption, urinalysis, haematology, serum biochemistry, and organ weights.